2019
DOI: 10.1128/jvi.01118-19
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative MA-CA Fusion Protein Is Incorporated into HIV-1 Cores and Inhibits Nuclear Entry of Viral Preintegration Complexes

Abstract: Particle maturation is a critical step in the HIV-1 replication cycle that requires proteolytic cleavage of the Gag polyprotein into its constitutive proteins: the matrix (MA), capsid (CA), nucleocapsid (NC), and p6 proteins. The accurate and efficient cleavage of Gag is essential for virion infectivity; inhibitors of the viral protease are potent antivirals, and substitutions in Gag that prevent its cleavage result in reduced HIV-1 infectivity. In a previous study, a mutation inhibiting cleavage at the MA-CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…Impairments in Gag processing can alter particle morphology and inhibit HIV-1 replication [32][33][34][35][36]. To test for evidence of budding defects and alterations to particle morphology upon depletion of IP5 and/or IP6, we examined infected MT-4 cells by thin section transmission electron microscopy at 3 days following infection.…”
Section: Depletion Of Ip6 Lowers Progeny Virion Infectivitymentioning
confidence: 99%
“…Impairments in Gag processing can alter particle morphology and inhibit HIV-1 replication [32][33][34][35][36]. To test for evidence of budding defects and alterations to particle morphology upon depletion of IP5 and/or IP6, we examined infected MT-4 cells by thin section transmission electron microscopy at 3 days following infection.…”
Section: Depletion Of Ip6 Lowers Progeny Virion Infectivitymentioning
confidence: 99%
“…****, P < 0.0001. (E) Mapped HIV NLX.Luc.R-U3-Tag -Luc integration sites in indicated cell lines; the EIAV U3-tagged virus affords integration site determinations in cells that harbor preexisting integrated LentiCRISPRv2 ( 66 ). See Table S1 for associated statistical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid psPAX2 was obtained from the NIH AIDS Reagent Program while plasmids pIRES2-eGFP ( 13 ), pNLX.LucR-U3-tag ( 66 ), and pCG-VSV-G ( 67 ) were previously described. Other plasmids that encoded single-round HIV-1 ( 68 ), HIV-2 ( 69 ), SIV agm Sab, SIV agm Tan ( 70 ), SIV mac ( 71 ), BIV ( 72 ), EIAV ( 73 ), FIV ( 74 ), and MLV ( 75 ) GFP constructs as well as HIV-1 (WT, N74D) ( 76 , 77 ), SIV mac ( 78 ), MLV ( 13 ), and FIV ( 79 ) Luc reporter viruses were also previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, blocking other cleavage events may impede virus replication by different mechanisms. For example, previous studies have shown that the uncleaved MA-CA Gag fragment is a very strong dominant negative HIV inhibitor with the ability to induce aberrant and eccentric core morphology, block reverse transcription in target cells, and disrupt proper nuclear entry and integration [ 191 , 192 ]. However, the MA-CA junction is unstructured [ 193 ] and, therefore, may not be readily inhibited by small molecules.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%